A socio-scientific reading of John 4: Lessons for the Zimbabwean Adventist church - Takawira, Tendai; Hombana, Mphumezi (Verbum et ecclesia, 2025)
The article explores Jesus’ interaction with the Samaritan woman in John 4 to uncover his inclusive perception of mission and the criteria for participation. It reveals that Jesus did not exclude individuals based on gender, ethnicity, class, or institutional power, but rather embraced all as worthy participants. Using socio-scientific models—honour-shame, collectivism, kinship, and character vilification—the study shows how Jesus subverted societal norms by elevating marginalised groups within the Johannine community. Drawing parallels with Zimbabwean cultural contexts, the article critiques the patriarchal ethos influencing the Seventh Day Adventist Church in Zimbabwe (SDAZ), which often limits mission participation based on gender and ethnicity. In contrast, Euro-American SDA churches tend to reflect Jesus’ inclusive model more closely. The study calls for the SDAZ and the global SDA Church to adopt Jesus’ radically inclusive approach to mission, as exemplified in John 4:1–42.Intradisciplinary and/or interdisciplinary implicationsThis study used a social-scientific reading of John 4:1–42 to examine how Jesus’ encounter with the Samaritan woman challenges power, ethnic and gender biases. It advocates for an inclusive mission model in the SDAZ and the SDA world church at large, thereby affirming women’s equal participation in spreading the Gospel mission.